Efektivitas Pelatihan Self-talk Dalam Menurunkan Stres Akademik Pada Mahasiswa Fakultas Psikologi Universitas Negeri Makassar - Devita Rezky Ramadhani; Ahmad Ridfah; Ismalandari Ismail (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Academic stress can have negative effects on students because it can disrupt psychological and physical well-being; therefore, self-talk is needed. This study aims to determine whether self-talk is effective in reducing academic stress among students of the Faculty of Psychology, Makassar State University. The participants in this study totaled 16 students, divided into two groups: 8 in the control group and 8 in the experimental group. This study used a true experimental research design with a pretest–posttest control group design. The scale used in this study had a reliability value of 0.754. The results showed a decrease in the mean score of academic stress in the experimental group, from 76.13 to 51.63, while the academic stress score in the control group changed from 64 to 63.75. The findings indicate that the Mann–Whitney test produced a p-value of 0.002 (p 0.05). The Wilcoxon test for the experimental group showed a significant decrease in academic stress scores after the treatment, with p = 0.006 (p 0.05). It can be concluded that self-talk is effective in reducing academic stress among students of the Faculty of Psychology, Makassar State University. Self-talk has been proven to reduce academic stress among these students.